Metalinguistic Reflection and Computer-Mediated Communication: An Interventionist approach to Language Study Abroad - McGregor, Meredith (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
This article reports on part of a mixed-methods study framed by sociocultural theory and aimed at assessing the impact of an intervention to promote metalinguistic awareness in language study abroad sojourners. Participants utilized a social media platform as a space to develop personalized e-portfolios for the purpose of in-depth metalinguistic reflection, paired with entirely computer-mediated researcher-participant mentoring. As such, this study addresses the importance of intervention in second language learning in study abroad, while also adding to the research available on its intersections within a 24/7 digitally connected world. Analysis of the data suggests that carrying out reflective practices and engaging with a mentor, even at distance, may be contributory in enhancing Spanish language proficiency. Further, this provides evidence that interventionist approaches to study abroad can be made accessible and meaningful even in the absence of significant resources, and without implementing prohibitively onerous tasks for either a student or practitioner.